Optimal packet size in error-prone channel for IEEE 802.11 distributed coordination function - Jun Yin; Xiaodong Wang; Agrawal, D.P. (2004 IEEE Wireless Communications and Networking Conference, 2004)
With the popularity of the IEEE 802.11 based wireless network, it has become increasingly important to analyze the performance of the IEEE 802.11 protocol accurately. Throughput and delay are key measures, reflecting the performance of a wireless network. In this paper, we analyze the performance of the IEEE 802.11 distributed coordination function (DCF) in the saturated traffic condition, and consider the effects of packet size, the number of contention nodes, transmission collision probability and channel conditions. Under this analytical framework, we evaluate the impact of error-prone channel on unsuccessful transmission probability and its impact on the performance. A trade-off exists between the desire to reduce the ratio of overhead in the data packet by adopting larger packet size, and the need to reduce the packet error rate in the error-prone environment by using smaller packet length. An optimal packet size can be derived to maximize the throughput of the IEEE 802.11 DCF under various channel conditions and network configurations. To validate our analytical results, we have done extensive simulations, and the simulation results are observed to match very well with the analytical results.